Análise simultânea dos conceitos da infância : crescimento, desenvolvimento, crescimento e desenvolvimento - Dantas, Ana Márcia Nóbrega (2023)
Objective: to simultaneously analyze the concepts of childhood, growth, development, growth and development. Method: this is a conceptual analysis, using the simultaneous concept analysis method, consisting of nine steps: 1) development of the consensus group; 2) selection of concepts to be analyzed; 3) refinement of the concept clarification approach; 4) clarification of individual concepts; 5) development of validity matrices; 6) review of the clarification of the individual concept; 7) reexamination of validity matrices; 8) development of the procedural model; 9) presentation of SCA results to peers for criticism. Results: validity matrices were constructed for the concepts, making it possible to identify elements that are particular to each concept as well as the similarities that bring them together. By carrying out simultaneous concept analysis, a broad and particular view of the phenomena studied was obtained. Elements such as “underweight”, “overweight”, “eating practices”, “physical activity” and “intrauterine growth” appeared associated with growth antecedents. The elements “social stimulation”, “genetic-environmental interaction” and “stimulation of social and imaginative play” for developmental antecedents. The elements of “growth and development” were: “socioeconomic determinants”, “cultural determinants”, “paternal and maternal factors” and “domestic environment”. In the attributes of the growth concept, one can observe “weight for age”, height”, “head circumference” and “body mass index for age”. Regarding development attributes: “Skills to use language”, “Fine and gross motor skills” and “Sensory skills”. The attribute elements common to growth and development are: “Neurocerebral maturation”, “Body maturation” and “Multidimensional”. The particular consequential elements of growth are “Healthy Growth” and “Identification in Growth Delay”; for development: “Identification of developmental delay” and “Cognitive capacity”; and the consequences of growth and development were found: “Grow and develop within normal limits”, “Reduction in mortality” and “Adequate oral and body hygiene”. Finally, the elements were validated by experts. Final considerations: the results showed that the concepts of growth and development are complex and multidimensional, making it possible to state that they are distinct, their differences can be observed, but also elements in common, visualized through antecedents, attributes and consequences.